STEAM-education in Uzbekistan: problems and prospects of development (Acta Education, 2024)
The article discusses the problems and prospects of the development of STEM education in Uzbekistan. The study identifies the main obstacles to the effective implementation of STEAM education, including a lack of material and technical base, a shortage of qualified teachers, outdated curricula, low student motivation and gender inequality. The article pays special attention to the need for an integrated approach to reforms in the STEAM education system to train highly qualified specialists who can contribute to economic growth and innovative development of Uzbekistan.